CDC20‐Mediated Selective Autophagy Degradation of PBRM1 Affects Immunotherapy for Renal Cell Carcinoma - Yizeng Fan; Weichao Dan; Taotao Que; Yi Wei; Bo Liu; Zixi Wang; Yulin Zhang; Yuzhao Wang; Tianjie Liu; Yanxin Zhuang; Mengxing Li; Chendong Guo; et al. (Advanced Science)
Abstract Polybromo 1 (PBRM1) inactivating mutations are associated with clinical benefit from immune checkpoint inhibitor treatments in clear cell renal cell carcinoma (ccRCC). However, whether targeting PBRM1 has the potential to enhance immunotherapy efficacy in patients with wild‐type PBRM1 and the upstream pathways that regulate PBRM1 protein stability remain unclear. Here, it is demonstrated that PBRM1 knockdown induced M1 macrophage polarization and infiltration, which enhanced the efficacy of anti‐PD‐1 immunotherapy in RCC. Meanwhile, CDC20 catalyzes K27 ubiquitination of PBRM1 and promotes its degradation via p62‐mediated selective autophagy. A bicyclic peptide (PB1‐p62) is designed and constructed to target PBRM1 and p62, thereby promoting the degradation of PBRM1. As a result, the efficacy of anti‐PD‐1 immunotherapy is enhanced, leading to improved overall survival rates in syngeneic mouse tumor models. Overall, this finding suggest the clinical application of PB1‐p62 and provide a novel approach for enhancing the effectiveness of immunotherapy in RCC patients with wild‐type PBRM1.